Constructing data-derived family histories using electronic health records from a single healthcare delivery system - Leventer-Roberts, Maya; Gofer, Ilan; Barak Corren, Yuval; Reis, Ben Y; Balicer, Ran (European journal of public health, 2020)
Abstract Background In order to examine the potential clinical value of integrating family history information directly from the electronic health records of patients’ family members, the electronic health records of individuals in Clalit Health Services, the largest payer/provider in Israel, were linked with the records of their parents. Methods We describe the results of a novel approach for creating data-derived family history information for 2 599 575 individuals, focusing on three chronic diseases: asthma, cardiovascular disease (CVD) and diabetes. Results In our cohort, there were 256 598 patients with asthma, 55 309 patients with CVD and 66 324 patients with diabetes. Of the people with asthma, CVD or diabetes, the percentage that also had a family history of the same disease was 22.0%, 70.8% and 70.5%, respectively. Conclusions Linking individuals’ health records with their data-derived family history has untapped potential for supporting diagnostic and clinical decision-making.